Konsep Ketuhanan: Kajian Terhadap Pemikiran Syeikh Ibn 'Ajibah dalam Tafsir Al-Bahr Al-Madid fi Tafsir Al-Quran Al-Majid - Sulaiman, Firdaus; Hj. Mohd Yusoff, Mohd Yakub @ Zulkifli (Online Journal of Research in Islamic Studies, 2016)
The concept of God is a major issue in the Islamic faith. Clerics and Islamic scholars agree that Tawhid is the basic principle of Islamic faith. However, they differ in approach to explain it. Shaykh Ibn 'Ajibah is among many scholars who discussed the concept of God in his Quranic exegesis book named Al-Bahr Al-Madid Fi Tafsir Al-Quran Al-Majid. This study will reveal the views and approaches of Shaykh Ibn 'Ajibah about some important issues relating to the concept of God in Islam. Among the issues are the concept of Tawhid, Af'al, Nature and Essence of Allah, the concept of Tajalli, RuÂ’yah of Allah, the concept Musyahadah and 'Ayan, and the concept Hulul and Ittihad. The study finds that Shaykh Ibn 'Ajibah had distinctive views and approaches in explaining the matters above. His views and approaches were clearly influenced by the doctrine of Sufism that he believed in.